Over the moon : the novelization - Shang, Wendy Wan Long (Harper, an imprint of HarperCollins Publishers, 2020)
"Fueled with determination and a passion for science, a bright young girl named Fei Fei builds a rocket ship to the moon to prove the existence of a legendary Moon Goddess. There she ends up on the adventure of a lifetime and discovers a whimsical land of fantastical creatures"--from Amazon.